43 Changes in the Incidence of Respiratory AIDS-Defining Events Among Persons with HIV Before vs. During the COVID-19 Pandemic - Jesse J. Carlson; Megan Turner; Austin Katona; Sean Kelly; Timothy R. Sterling; Peter F. Rebeiro (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: The COVID-19 pandemic disrupted HIV care, though it prompted preventive measures for respiratory pathogens, particularly among PWH. We therefore quantified trends in respiratory ADE incidence during vs. before the COVID-19 pandemic to assess effects of these measures on non-COVID-19 illnesses. METHODS/STUDY POPULATION: We included PWH aged ≥18 years in care at the Vanderbilt Comprehensive Care Clinic in Nashville, Tennessee from 2017-2023. Individuals contributed time from the last of March 31, 2017 or clinic enrollment until the first of death, March 31, 2023 (study close), or final clinic visit (if there was no visit ≤12 months before study close). We described respiratory ADE incidences (per 1,000 person-years) in each year of the study; we used Poisson regression with robust variance to estimate the incidence rate ratio (IRR) and 95% confidence interval (CI) for respiratory ADEs in the three years following vs. before the World Health Organization’s pandemic designation for COVID-19 (March 2020). RESULTS/ANTICIPATED RESULTS: Among 4,880 persons contributing 19,510 person-years, 69 (1.4%) developed ≥1 respiratory ADE. Median age at cohort entry was 42.6 (interquartile range [IQR]: 32.1, 52.3) years and at first respiratory ADE was 43.6 (IQR: 36.1, 51.2) years. The overall average respiratory ADE incidence in the pre-pandemic period (March 2017-March 2020) was 4.5 (95% CI: 3.3-6.3) per 1,000 person-years and during the post-pandemic period (April 2020-March 2023) was 4.1 (95% CI: 1.8-9.0) per 1,000 person-years. When accounting for repeated outcomes and annual variation, the modeled respiratory ADE incidence was 10% lower (IRR=0.9, 95% CI: 0.6-1.4) during vs. before the COVID-19 pandemic. DISCUSSION/SIGNIFICANCE: Respiratory ADE incidence dropped 10% following the COVID-19 pandemic declaration, though the confidence interval for this change contains the null. It is plausible that nonpharmaceutical COVID-19 mitigation measures drove a brief but impermanent decline, though further research is needed to assess whether diagnostic biases also played a role.